A Study on the Relationship between Climate Change and Peak Discharge in Sarawak River Basin - Syed Almunir, Bin Mohd Zarak; Adam, J.H. (Universiti Malaysia Sarawak, (UNIMAS), 2013)
These Earth's climate is getting warmer, and the signs are everywhere. Abnormal river discharge is one of the impacts that can be found in local scale. This endangering condition leads to the necessary attention on river basin in Sarawak, Malaysia and hence gives birth to this study. The objective of this study is to examine the existence of climate change on Sungai Sarawak River Basin through a hydrologic analysis of river discharge of three water level stations: Station Rayu, Station Git and Station Buan Bidi. The methods applied are mass-curve coupled with Gumbel’s graphical statistical method and annual hydrograph. Mass curve plotted shows the deviation of cumulative peak discharge from its original trend with Stations Rayu, Git and Buan Bidi started straying since years 1998, 2001 and 2004 respectively. After breakpoint, Gumbel’s graphical statistical method for chance percent evaluation clearly implies the chance percent for all (exception for Station Buan Bidi) discharges has decreased throughout the years. Whereas Gumbel’s graphical statistical method for return period evaluation suggested an extension of return period after the transition year (exception for Station Rayu). Two graphical methods pointed to the same direction – rate of decline shifting is greater for high flow as compared to low flow. Broadly speaking, precipitation has not much effect on the discharge variation according to annual hydrographs plotted. However, an obvious decrease in monthly average discharge throughout 18 years was found after change at Station Rayu. This support the climate change fact of “dry getting drier”. Water shrinkage in Sarawak River Basin is expected to be experienced frequently in the future.